Disrupting the Cdk9/Cyclin T1 heterodimer of 7SK snRNP for the Brd4 and AFF1/4 guided reconstitution of active P-TEFb. Issue 2 (22nd December 2021) - Zhou, Kai; Zhuang, Songkuan; Liu, Fulong; Chen, Yanheng; Li, You; Wang, Shihui; Li, Yuxuan; Wen, Huixin; Lin, Xiaohua; Wang, Jie; Huang, Yue; He, Cailing; et al.
Abstract: P-TEFb modulates RNA polymerase II elongation through alternative interaction with negative and positive regulation factors. While inactive P-TEFbs are mainly sequestered in the 7SK snRNP complex in a chromatin-free state, most of its active forms are in complex with its recruitment factors, Brd4 and SEC, in a chromatin-associated state. Thus, switching from inactive 7SK snRNP to active P-TEFb (Brd4/P-TEFb or SEC/P-TEFb) is essential for global gene expression. Although it has been shown that cellular signaling stimulates the disruption of 7SK snRNP, releasing dephosphorylated and catalytically inactive P-TEFb, little is known about how the inactive released P-TEFb is reactivated. Here, we show that the Cdk9/CycT1 heterodimer released from 7SK snRNP is completely dissociated into monomers in response to stress. Brd4 or SEC then recruits monomerized Cdk9 and CycT1 to reassemble the core P-TEFb. Meanwhile, the binding of monomeric dephosphorylated Cdk9 to either Brd4 or SEC induces the autophosphorylation of T186 of Cdk9. Finally, the same mechanism is employed during nocodazole released entry into early G1 phase of cell cycle. Therefore, our studies demonstrate a novel mechanism by which Cdk9 and CycT1 monomers are reassembled on chromatin to form active P-TEFb by its interaction with Brd4 or SEC to regulate transcription.